Impacts of sugarcane farming on coastal wetlands of the north coast of Zululand, Kwadukuza, South Africa - Matavire, Melisa M. (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2015.